Transformation of Morinda citrifolia via simple mature seed imbibition method - J.J, Lee; S, Ahmad; H.A, Roslan (Asian Network for Scientific Information, 2013)
View at Publisher| Export | Download | Add to List | More... Pakistan Journal of Biological Sciences Volume 16, Issue 24, 2013, Pages 1913-1921 Transformation of Morinda citrifolia via simple mature seed imbibition method (Article) Lee, J.J., Ahmad, S., Roslan, H.A. Department of Molecular Biology, Universiti Malaysia Sarawak, 94300 Kota Samarahan, Sarawak, Malaysia View references (44) Abstract Morinda citrifolia, is a valuable medicinal plant with a wide range of therapeutic properties and extensive transformation study on this plant has yet been known. Present study was conducted to establish a simple and reliable transformation protocol for M. citrifolia utilising Agrobacterium tumefaciens via direct seed exposure. In this study, the seeds were processed by tips clipping and dried and subsequently incubated in inoculation medium. Four different parameters during the incubation such as incubation period, bacterial density, temperature and binary vectors harbouring β-glucuronidase (GUS) gene (pBIl 21 and pGSAl 131), were tested to examine its effect on transformation efficiency. The leaves from the treated and germinated seedlings were analysed via Polymerase Chain Reaction (PCR), histochemical assay of the GUS gene and reverse transcription-PCR (RT-PCR). Results of the study showed that Agrobacterium strain LBA4404 with optical density of 1.0 and 2 h incubation period were optimum for M. citrifolia transformation. It was found that various co-cultivation temperatures tested and type of vector used did not affect the transformation efficiency. The highest transformation efficiency for M. citrifolia direct seed transformation harbouring pBI121 and pGSAl 131 was determined to be 96.8% with 2 h co-cultivation treatment and 80.4% when using bacterial density of 1.0, respectively. The transformation method can be applied for future characterization study of M. citrifolia.